Generative power and closure properties of Watson-Crick grammars - Mohamad Zulkufli, Nurul Liyana; Turaev, Sherzod; Mohd Tamrin, Mohd Izzuddin; Messikh Azeddine, Azeddine (Hindawi Publishing Corporation, 2016)
We define WK linear grammars,as an extension of WK regular grammars with linear grammar rules,and WK context-free grammars, thus investigating their computational power and closure properties. We show that WK linear grammars can generate some context sensitive languages. Moreover, we demonstrate that the family of WK regular languages is the proper subset of the family of WK linear languages, but it is not comparable with the family of linear languages. We also establish that the Watson-Crick regular grammars are closed under almost all of the main closure operations.